ANALISIS PENGARUH IKLAN DAN CELEBRITY ENDORSER TERHADAP PENDAPATAN ONLINE SHOP DI KOTA PALU - Jaya, Andi Herman; Parinding, Kalvin A. (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2024)
This study aims to analyze the impact of advertising and Celebrity Endorser on online shop revenue in Palu city. The method used in this research is multiple linear regression analysis. Data was collected through interviews and questionnaires given to 40 online shop actors in Palu city. The data analysis used includes classical assumption test, multiple linear regression test, hypothesis testing, and Determinant coefficient test (R2). The results showed that the advertising variable and the Celebrity Endorser variable contributed 0.49 percent to the revenue of online shops in Palu city. The regression coefficient of the advertising variable is 0.214 which shows a positive influence, while the regression coefficient of the Celebrity Endorser variable is 0.122 which also shows a positive influence. Thus, this study provides evidence that advertising and Celebrity Endorser have an important role in increasing online shop revenue in Palu city. Online shop actors in Palu city can utilize advertising strategies and Celebrity Endorsers to increase their income. This research also contributes to the understanding of the factors that influence online shop revenue and can be a reference for further research in this field.